An Overview of the Use of Milk Preservatives for Shelf-Life Extension - Ahmadi, Sayed Arif (Journal of Natural Sciences – Kabul University, 2025)
Preservatives are substances that, when added in small amounts to milk and dairy products, can inhibit and delay fermentation, acidification, or other decomposition. The importance of using preservatives to prevent or slow the spoilage of dairy products is significant. In this review, the use of preservatives in milk and its products has been examined using articles, reports, and reliable online sources, including the World Health Organization. The findings show that milk and dairy products can contain live microbes and pathogens; therefore, the use of preservatives is necessary to extend their shelf life. Due to technical and economic constraints in some developing countries, the use of refrigerators and freezers is not feasible, and preservatives are inevitably used to maintain the quality and safety of dairy products.